Power system security assessment in electrical operation system - Maikale, Babagana Digol (2021)
Power system security and assessment are important tasks in modern energy management systems. The present trend towards deregulation and the need for new transmission expansion due to load growth or generation expansion has forced modern electric utilities to operate their systems under stressed operating conditions closer to their security limits. The purpose of security assessment is to provide information to the system operators about the secure and insecure nature of the operating states in the event of any contingency, so that proper control/corrective action can be initiated within the safe time limit. Power system security must be concerning all the time to ensure that the system always operate in a good condition. To make sure that the system operates in a good condition, security assessment must be done on the current system. Thus, this project performed power system security and assessment on 14 Buses, the work is done to identify faulty Buses and lines in order to take prompt action to sure that there is no problem occurs at the transmission line such as power overload and no voltage violation occurs at Bus when one or two of the transmission lines are eliminated. If there is a power overload in the system, contingency analysis must be done on the system to secure back the system. To secure back the system, transmission line of the system must be rank first according to its severity level by using appropriate assessment method. (N-1) contingency analysis has been used to assess the security level of the test system. In this project, Matlab software is used for the analysis and IEEE 14-Bus system is used as the test system. This project only focusses on the transmission line capacity in the system and the voltage changes at the Bus. The system was tested 4 different conditions, these include normal conditions, 5% Overloaded, 10% overloaded, 15% overloaded, 20% overloaded. The project was successfully done with all contingencies analysed. Hence, this project has conducted security assessment on 14 Bus power system and will provide reliable data for future power system assessment and operation.